TINJAUAN HUKUM TERHADAP PENJUALAN WARISAN OLEH AHLI WARIS TANPA PERSETUJUAN SEBAGIAN AHLI WARIS (STUDI KASUS PUTUSAN PENGADILAN TINGGI AGAMA NOMOR 96/PDT.G/2014/PTA MDN) - ANIFAH SITOMPUL (PREMISE LAW JURNAL, 2018)
The procedure of legal provision on land right transfer because of inheritance, based on the Decree of the Minister of Agrarian Affairs/the head of the National Land Agency No. 3/1997 on Land Registration is that the petitioner as the heir/his attorney files a request for transfer registration by submitting Land Certificate in the name of the heir. Death Certificate in the name attached in the certificate, affidavit in the from of a will, the Court’s Verdict, Judge’s Decision, and heirs’ identity cards. If there is more than one heir, the registration for transfer has to be accompanied by a certificate of inheritance distribution containing notification about the land or building rights which is based on the Corticated of the distribution of the inheritance. If the Land is a grant, the above certificates have to be attached by the certificate of grant/will plus BPHTB ( Duty on Land and Building Rights Acquisition), but if the grant is stiil uncertain, the transfer registration has to be done by heirs and grant receiver and it is considered as joint property. In order to avoid loss of the parties as in the Religious Court’s Verdict No. 96/Pdt.G/2014/PTA.Mdn, the implementation of inheritance distribution has to be done according to legal certaintyby recognizing the process of inheritance land ownership with the prudential principles to ward off legally defective Notarial deed by checking the Certificate of transferring inheritance before the Notary/PPAT, supporting by the evidence of heirs’ approval by checking the land location, getting information about the labd ownership from neighbors, examining the other supporting data, with the seller’s and the buyer’s good faith. The Religious Court’s Verdict No.96/Pdt/2014/PTA. Mdn provides legal protection for the buyer by revoking the Religious Court’s Verdict, Medan, and foreclosure on the case object is considered invalid.Keywords: Court’s Verdict, Grant receiver, Considered as Joint Property